Status Hukum Pernikahan Saudara Tiri Perspektif Hukum Keluarga Islam - Ismail, Habib; Ja'far, A. Kumedi (Kartika: Jurnal Studi Keislaman, 2024)
Marriage between stepsiblings, in the perspective of Islamic family law, is an issue that often sparks debate, both legally and socially. In general, scholars agree that marriage between stepsiblings is permissible in Islam because they do not fall under the category of mahram (forbidden relatives) who are prohibited from marrying. This study aims to examine in depth the Islamic legal perspective regarding marriage between stepsiblings and explore the social and cultural implications that may arise in the practice of such marriage. By understanding this, it is hoped that a clearer understanding of the legal and social aspects of marriage between stepsiblings can be achieved and provide valuable insights into the context of Islamic family law and civil law in Indonesia. This qualitative research aims to explain the Islamic legal perspective on marriage between stepsiblings. The study focuses on understanding marriage between stepsiblings within the context of Islamic family law and how this phenomenon is accepted and viewed from society's social and cultural perspectives. The method used is descriptive research, which explains marriage between stepsiblings from the perspective of Islamic family law. The results of this study indicate that marriage between stepsiblings, according to Islamic family law, is permissible under Islamic jurisprudence (fiqh) and Indonesian civil law. Scholars, including Imam an-Nawawi, agree that stepsiblings are not considered mahram and thus are not prohibited from marrying because their relationship does not stem from direct blood ties or lineage but rather from the marriage of their parents. Therefore, marriage between stepsiblings is valid under Islamic law as long as there is no direct blood relation between them.